IMPLICATIONS OF PERSON-JOB FIT AND COMPETENCY ON EMPLOYEE PERFORMANCE AT THE CENTRAL SULAWESI EDUCATION OFFICE - Dila Safiah; Yoberth Kornelius; Niluh Putu Evvy Rossanty; Mohammad Ali Murad (RADJA PUBLIKA, 2026)
This study aims to analyze the implications of person-job fit and competence on employee performance at the Central Sulawesi Education Office. The study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to 55 employees as the research sample, which was determined using the Slovin formula. Data analysis was performed using multiple linear regression using SPSS. The results of the study indicate that partially person-job fit has no significant effect on employee performance, while competence has a positive and significant effect on employee performance. Simultaneously, person-job fit and competence have a positive and significant effect on employee performance with a coefficient of determination of 0.797, indicating that both variables are able to explain 79.7% of the variation in employee performance. These findings indicate that increasing employee competence is a major factor in improving performance, while person-job fit will be more effective if supported by adequate competence. The results of this study are expected to be a consideration for agencies in human resource management, especially in efforts to improve employee performance.